Aviation psychology and human factors - Martinussen, Monica; Hunter, David R. (David Robert), 1945- (Boca Raton : Taylor & Francis, CRC Press, 2017)
This book covers the application of psychological principles and techniques to situations and problems of aviation. It offers an overview of the role psychology plays in aviation, system design, selection and training of pilots, characteristics of pilots, safety, and passenger behavior. It covers concepts of psychological research and data analysis and shows how these tools are used in the development of new psychological knowledge. The new edition offers material on physiological effects on pilot performance, a new chapter on aviation physiology, more material on fatigue, safety culture, mental health and safety, as well as practical examples and exercises after each chapter.--Provided by publisher.
chapter 1 Introduction -- chapter 2 Research Methods and Statistics -- chapter 3 Aviation Physiology -- chapter 4 Abilities and Personality Traits -- chapter 5 Personnel Selection -- chapter 6 Training -- chapter 7 Human Factors and the Design of Aviation Systems -- chapter 8 Stress and Human Reactions -- chapter 9 Culture, Organizations, and Leadership -- chapter 10 Aeronautical Decision-Making -- chapter 11 Aviation Safety -- chapter 12 Concluding Remarks.
Includes bibliographical references.
Keywords: Aircraft accidents -- Human factors; Aviation psychology; Flight -- Physiological aspects